2020
DOI: 10.3390/microorganisms8081150
|View full text |Cite
|
Sign up to set email alerts
|

Planctomycetes as a Vital Constituent of the Microbial Communities Inhabiting Different Layers of the Meromictic Lake Sælenvannet (Norway)

Abstract: Meromictic lakes are permanently stratified lakes that display steep gradients in salinity, oxygen and sulphur compounds tightly linked to bacterial community structure and diversity. Lake Sælenvannet is a meromictic lake located south of Bergen, Norway. The 26 m deep lake is connected to the open sea and permanently stratified into two layers separated by a chemocline. The upper water layer is brackish with major input from water runoff from the surroundings. The bottom layer consists of old saline water with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Planctomycetes were present in all four Stuckberry Lakes (Figure 3), as expected given the wide freshwater distribution of this group (Zwart et al, 2002;Newton et al, 2011). These heterotrophs have various important ecosystem functions, including contributing to the degradation of complex organic compounds (Schlesner et al, 2004;Fuchsman et al, 2012), and they are mostly found in the hypolimnia of deep oxygenated lakes (Okazaki and Nakano, 2016;Karlov et al, 2017;Okazaki et al, 2017;Storesund et al, 2020). By contrast, 2FB Lake, where Planctomycetes reached their greatest relative abundances in our dataset (40%) (Figure 3C), was shallow and hypoxic.…”
Section: Fb Lakesupporting
confidence: 78%
“…Planctomycetes were present in all four Stuckberry Lakes (Figure 3), as expected given the wide freshwater distribution of this group (Zwart et al, 2002;Newton et al, 2011). These heterotrophs have various important ecosystem functions, including contributing to the degradation of complex organic compounds (Schlesner et al, 2004;Fuchsman et al, 2012), and they are mostly found in the hypolimnia of deep oxygenated lakes (Okazaki and Nakano, 2016;Karlov et al, 2017;Okazaki et al, 2017;Storesund et al, 2020). By contrast, 2FB Lake, where Planctomycetes reached their greatest relative abundances in our dataset (40%) (Figure 3C), was shallow and hypoxic.…”
Section: Fb Lakesupporting
confidence: 78%
“…However, the role Geothrix plays in reducing metal ions makes the bacteria environmentally essential. Planctomycetes are ubiquitous in both aquatic and soil ecosystems, and they are mostly chemoorganotrophic microorganisms that break down complex organic compounds [38]. In the river, this phylum contained Pirellula, Blastopirellula, Candidatus Annammoximicrobium moscowii, which was discovered as a novel microorganism involved with anaerobic ammonium oxidation for treatment of filtrate of wastewater fermented residue [39].…”
Section: Discussionmentioning
confidence: 99%
“…The first report of the isolation of a planctomycete in axenic cultures is due to the work of James T. Staley (Staley, 1973). During the last decade, several members of Planctomycetes were isolated in pure culture and described as representing new genera, namely Schlesneria (Kulichevskaya et al, 2007b), Singulisphaera (Kulichevskaya et al, 2008;Kulichevskaya et al, 2012a), Zavarzinella (Kulichevskaya et al, 2009), Aquisphaera (Bondoso et al, 2011), Telmatocola (Kulichevskaya et al, 2012b), Paludisphaera (Kulichevskaya et al, 2016;Kaushik et al, 2020), Roseimaritima (Bondoso et al, 2015;Kumar et al, 2020b), Rubripirellula (Bondoso et al, 2015;Kallscheuer et al, 2019b), Fimbriiglobus (Kulichevskaya et al, 2017a), Tundrisphaera (Kulichevskaya et al, 2017b), Mariniblastus (Lage et al, 2017), Caulifigura (Kallscheuer et al, 2020a), Tuwongella (Seeger et al, 2017), Crateriforma (Peeters et al, 2020c), Fuerstia (Kohn et al, 2016;Kohn et al, 2019), Novipirellula (Kallscheuer et al, 2019c), Tautonia (Kovaleva et al, 2019;Jogler et al, 2020) Limnoglobus (Kulichevskaya et al, 2020b), Thalassoglobus (Kohn et al, 2020a;Rivas-Marin et al, 2020c), Symmachiella (Salbreiter et al, 2020), Gimesia (Scheuner et al, 2014;Kumar et al, 2020a;Wang et al, 2020), Stieleria (Sandargo et al, 2020;Storesund et al, 2020;Surup et al, 2020), Aureliella (Kallscheuer et al, 2020b), Maioricimonas (Rivas-Marin et al, 20...…”
Section: Cultured Planctomycetesmentioning
confidence: 99%